2011
DOI: 10.1002/jclp.20838
|View full text |Cite
|
Sign up to set email alerts
|

Struggling and enduring with God, religious support, and recovery from severe mental illness

Abstract: Religious variables, including religious support and spiritual struggle, might affect recovery from severe mental illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 75 publications
3
32
0
Order By: Relevance
“…Negative religious coping has been associated with poorer health outcomes in other studies (33)(34)(35). In our present study, we also found that religious coping styles that were more negative were associated with worse adherence (33)(34)(35).…”
Section: Original Researchsupporting
confidence: 81%
See 1 more Smart Citation
“…Negative religious coping has been associated with poorer health outcomes in other studies (33)(34)(35). In our present study, we also found that religious coping styles that were more negative were associated with worse adherence (33)(34)(35).…”
Section: Original Researchsupporting
confidence: 81%
“…Negative religious coping has been associated with poorer health outcomes in other studies (33)(34)(35). In our present study, we also found that religious coping styles that were more negative were associated with worse adherence (33)(34)(35). However, what was unexpected was that superadherent parents reported using negative religious coping more frequently than high-adherent parents did.…”
Section: Original Researchsupporting
confidence: 70%
“…In particular, a number of studies look at the lived experience of involuntary hospitalizations during the acute phase of the disease (Williams, 2008;Wood & Pistrang, 2008). In contrast, a vast amount of literature explores solely the lived experience of the recovery process (Aston & Coffey, 2012;Dilks, Takser, & Wren, 2010;Jensen & Wadkins, 2007;Turton et al, 2011), or the coping mechanisms used to combat mental illness (Green, Hayes, Dickinson, Whittaker, & Gilheany, 2002;Webb, Charbonneau, McCann, & Gayle, 2011;Yangarber-Hicks, 2004), whilst others investigate the ambivalent relationship between medication and quality of life (Gale et al, 2012;Piat et al, 2009;Sajatovic & Jenkins, 2007). Furthermore, some other studies describe the relationship between mentally ill people and health care professionals (Borg & Krinstiansen, 2004;Cleary, Hunt, Horsfall, & Deacon, 2012;Gahnström-Strandqvist, Josephsson, & Tham, 2004;McCloughen, Gillies, & O'Brien, 2011;Schroeder, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…In a study of 241 college undergraduates, spiritual struggle partially mediated the relationship between trauma and post-traumatic stress disorder symptoms (Wortmann, et al, 2011). Webb and colleagues reported that increased spiritual struggle predicted poorer recovery from mental diseases in a sample of 81 adults, and that this was mediated by religious support (Webb, Charbonneau, McCann, & Gayle, 2011). …”
Section: Association Of Spiritual Struggle With Healthmentioning
confidence: 99%